Мiшана задача для нелiнiйного параболiчного рiвняння з другою похiдною за часом в необмеженiй областi - Лавренюк, С.П.; Торган, Г.Р. (Видавничий дім "Академперіодика" НАН України, 2008)
We have obtained some sufficient conditions of existence of a generalized solution of the initial boundary-value problem for a nonlinear parabolic equation of the fourth order with the second time derivative in an unbounded domain with respect to spatial variables.